PENGARUH ASIMETRI INFORMASI, BOOK TAX DIFFERENCES, INVESTMENT OPPORTUNITY SET DAN STRUKTUR MODAL TERHADAP KUALITAS LABA - Zulanar Hasna; Muhammad Abdul Aris (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study basically aims to determine the effect of information asymmetry, book tax differences, investment opportunity set and capital structure on earnings quality. With a quantitative approach, the population in this study is an annual report on manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange in 2018-2020. Secondary data in this study were collected from www.idx.com.id and the websites of each company. The sampling process in this study used a purposive sampling method and obtained 116 data as the final sample. The technique used in the data testing process in this study is a multiple linear regression analysis technique with SPSS version 25. The results of this study indicate that information asymmetry with a significant level of 10% and capital structure with a significant level of 5% has a significant effect on earnings quality. Meanwhile, book tax differences and investment opportunity set have no significant effect on earnings quality.